Audit partner independence and business affiliation: evidence from Taiwan. (September 2019) - Chang, Yu-Shan; Chiang, Chia-Yu; Liu, Li-Lin (Sunny); Xie, Xinmei (Lucy)
Abstract: Affiliated business groups play important roles in markets, especially emerging markets. Both International Auditing and Assurance Standards Board (IAASB) and Public Company Accounting Oversight Board (PCAOB) have expressed strong concerns about the audit quality of group financial statements. Audit quality is closely related with auditor independence (Tepalagul & Lin, 2015). In this study, we examine whether audit partners are more likely to compromise their independence for clients affiliated with consolidated business groups. We incorporate the impact of business group in the construction of client importance proxy in order to explore the potential impact of clientele's business group affiliation. Our findings support that there is no evidence on Big N audit partners compromising their independence for economically important clients no matter whether the clients are affiliated or not. However, we find that the previously documented relation between client importance and audit partner independence in non-Big N audit partners rests with business-group-affiliated and unlisted clients. Therefore, we conclude that non-Big N audit partners tend to compromise their independence for economically important clients who are within affiliated business groups and not listed in stock exchanges.